Pengaruh literasi keuangan, gaya hidup, dan sikap keuangan terhadap manajemen keuangan (Studi pada mahasiswa Akuntansi Universitas Sam Ratulangi Manado) - Makahinda, Edgar Eleazar; Lambey, Robert; Rondonuwu, Sintje (Manajemen Bisnis dan Keuangan Korporat, 2025)
This study is motivated by financial issues arising in the digital finance era, where financial management serves as a solution to these problems. The purpose of this research is to empirically examine the influence of financial literacy, lifestyle, and financial attitudes on personal financial management. The object of this research is Accounting Students at Sam Ratulangi University, Manado, and the type of research applied is quantitative research using primary data. The sample was determined through a non-probability sampling method with purposive sampling technique. The results indicate that lifestyle and financial attitudes have a significant positive influence on financial management, while financial literacy shows no significant effect. Simultaneously, the three variables have a significant influence on student financial management, explaining 40.9% of the variation in financial management.